Pengembangan Kuis Interaktif Mobile untuk Tahfizh Al-Qur’an dengan Metode MDLC: Development of a Mobile Interactive Quiz for Memorizing the Qur'an Using the MDLC Method - Denny Cahyadi Sundara; Jefri Marzal; Rizqa Raaiqa Bintana (Jurnal Pendidikan Sains dan Komputer, 2026)
This study aims to design and build a mobile-based interactive quiz application as a learning medium at Attaufiq Jambi Private Islamic Elementary School. The research background stems from the need for more engaging and interactive learning media, particularly to support memorization of the Qur'an, which has so far relied on conventional, monotonous methods. To address this issue, this study uses the Multimedia Development Life Cycle (MDLC), which comprises six stages: concept, design, material collection, assembly, testing, and distribution. The application is named Attaufiq Quiz, with main features including interactive quizzes, audio recitations, and simple yet attractive visual displays. The material presented focuses on short surahs from Juz 30 that are relevant to the elementary school curriculum, enabling students to learn independently or with teachers. The test results show that this application meets the functional requirements, with all features running as designed. Subject teachers' validation of the material found that the quiz content is in accordance with the curriculum and suitable for use.In contrast, language validation found that the language used conforms to Indonesian language rules. The final stage, a Perceived Ease of Use (PEOU) test, was conducted with 22 sixth-grade students, yielding a score of 91.27% and a rating of very good. Thus, the Attaufiq Quiz app is considered easy to use and can support memorizing the Quran more effectively, interactively, and enjoyably.